Nuclear forensic analysis - Moody, Kenton James; Hutcheon, Ian D.; Grant, Patrick M. (CRC Press, Taylor & Francis Group, 2015)
The authors focus particularly on the chemical, physical, and nuclear aspects associated with the production or interrogation of a radioactive sample. They consolidate fundamental principles of nuclear forensic analysis, all pertinent protocols and procedures, computer modeling development, interpretational insights, and attribution considerations.